Parliamentary Bureaucratic Dualism and Legislative Productivity: Between Administration and Politics - Zúñiga Ramírez, César A. (2014)
This article explores the relations between the political manage of legislative factions and the technical-administrative support of the Costa Rican parliament from the point of view of the bills procedures efficiency and effectiveness. In a constructivist way, with the participation of various parliament consultants and experts in front of quantitative data related to parliament efficiency, the study suspects that the relation between political and technical-administrative consultants of the parliament breaks the Administrative Science concept of team work. In that perspective, it minimizes the legislative productivity of the parliament which requires democracy.